Effects of Multimedia Assisted Song Integrated Teaching on College Students' English Learning Interests and Learning Outcomes - Luo, Yu-Zhou; Kong, Xiang-Yang; Ma, Yu-Yang (Frontiers in Psychology, 2022)
In the process of globalization, the English language not only represents British and American culture, but it has also gradually become a language used all over the world, and it has become essential for many people to learn it as a second language. Education is the century business of a nation. At the same time, to meet the needs of E generation, I generation, and touch-screen generation students, teachers are increasingly undertaking multimedia-integrated curriculum design and instruction. Teachers are no longer knowledge providers, but they are expected to provide students with a personalized learning model and guide and support them in a timely manner. This study included a sample of business students from Guilin University of technology. A total of 216 students participated in a 16-week (3 h per week, a total of 48 h) course of experimental teaching. The research results showed that 1. multimedia assisted, song integrated English teaching affected learning interest, 2. That multimedia assisted, song integrated English teaching affected learning outcomes, and 3. That learning interest had significantly positive effects on learning outcome. Based on these results, this study contributes to improving college students' English listening, speaking, reading, and writing skills via multimedia teaching, which also facilitated their interest and ability to achieve the learning outcomes.